El género literario cuento como instrumento didáctico para desarrollo de la lectura en clase de E/LE para alumnos del 1º año en la escuela Sistema de Ensino Vestibulando Abaetetuba-PA - BOTELHO, Andréia Coutinho (2021)
Literature as a possibility of teaching / learning languages, presents numerous strategies for the acquisition of a second language. Therefore, this article aims to present the use of the literary genre story as a teaching tool to develop reading in E/LE class for students of the 1st year at the School of Sistema de Ensino Vestibulano in Abaetetuba-Pá, as a mechanism for teaching and learning Spanish language. As it is an instrument capable of activating in the student / learner the interest and willingness to study a new language, favoring the construction of knowledge through the use of literary text, specifically the story, entertainment and interaction genre, facilitating its development in The learning process of a foreign language, then, its benefits are many: motivation, development of the student's imagination, stimulates curiosity, favors knowledge of other cultures, increases pleasure and stimulation for reading, which is fundamental in our work. As for the methodological procedures, the research was carried out by means of a bibliographic review and a qualitative research, specifically a field study, through the application of the didactic sequence and questionnaire for students to answer in class. Therefore, several authors were used, among them we can highlight Marcuschi (2003), Baktin, (1992), Pastor (2004), Martín (2010).